Association of cognitive biases with human papillomavirus vaccine hesitancy: a cross-sectional study. Issue 5 (3rd May 2020) - Pomares, Tiffany D.; Buttenheim, Alison M.; Amin, Avnika B.; Joyce, Caroline M.; Porter, Rachael M.; Bednarczyk, Robert A.; Omer, Saad B.
ABSTRACT: Given the link between vaccine hesitancy and vaccine-preventable disease outbreaks, it is critical to examine the cognitive processes that contribute to the development of vaccine hesitancy, especially among parents of adolescents. We conducted a secondary analysis of baseline data from a two-phase randomized trial on human papillomavirus to investigate how vaccine hesitancy and intent to vaccinate are associated with six decision-making factors: base rate neglect, conjunction fallacy, sunk cost bias, present bias, risk aversion, and information avoidance. We recruited 1, 413 adults residing in the United States with at least one daughter aged 9–17 years old through an online survey on Amazon Mechanical Turk. Vaccine hesitancy, intent to vaccinate, and susceptibility to cognitive biases was measured through a series of brief questionnaires. 1, 400 participants were in the final analyzed sample. Most participants were white (74.1%), female (71.6%), married (75.3%), and had a college or graduate/professional education (88.8%). Conjunction fallacy, sunk cost bias, information avoidance, and present bias may be associated with vaccine hesitancy. Intent to vaccinate may be associated with information avoidance. These results suggest that cognitive biases play a role in developing parental vaccine hesitancy and vaccine-related behavior.